Breeding, Genetics, and Genomics of Ornamental Plants - Krishna Bhattarai; Johan Van Huylenbroeck (Horticulturae, 2022)
Ornamental crops include a broad range of plants, including herbaceous seasonal flowers to woody perennial trees [...]